Self-perception toward reading and the academic reading achievement of intermediate students of Saint Andrew's school: implications for a reading program - Mercado, Catherine T. (Animo Repository, 1999)
This study looks into the relationship between self-perception toward reading and the academic reading achievement of intermediate students of St. Andrew's School for the school year 1997-1998.The subjects of this study were 90 intermediate students of St. Andrew's School thirty subjects, arranged alphabetically, were taken from each grade level (grades 4-6), reflecting a systematic kind of sampling. This kind of sampling was used in the selection of students to come up with only 20 percent of the accessible population of 420.The way students felt about themselves as readers was measured by the 33-item Reader Self-Perception Scale by Henk and Melnick (1992). In this scale, all responses were recorded according to the four factors of self-efficacy in reading, namely: Progress, Observational Comparison, Social Feedback, and Physiological States. In this scale, students were asked to agree or disagree with each item using the five-point scale where students' scores in each factor were interpreted in terms of proportion until the overall scores were computed to reflect their overall self-perception of themselves as readers.Pearson's Product - Moment Correlation Coefficient was used to test whether there was a significant relationship that existed between self-perception toward reading and the academic reading achievement of the sample population. The obtained correlations coefficients were then subjected to a t test to test their significance. The following are the findings of the study: 1. With the use of the mean and the standard deviation, out of 90 students included in the sample population, only 18 got a high reader self-perception.2. The students' grades in the academic reading achievement are less varied as compared with their scores in the Reader Self-Perception Scale.3. There is no significant relationship between students' self-perception toward reading and their academic reading achievement (r=0.090, p.05) thus, the null hypothesis is accepted.4. A student's self-perception toward reading is found to have no bearing on his academic reading achievement. This means that even if one has low perception of himself as a reader, this does not deter him from achieving academically because his motivation propels him to engage in reading activities. This practice in turn leads to his acquisition of knowledge, which is an important factor in academic success. The study formulated the following conclusions:1. Self-perception toward reading of intermediate students of St. Andrew's School for the school year 1997-1998 is independent of their academic reading achievement. A low perception of oneself as a reader, does not deter one from being motivated to value reading and learning.2. The reading program of St. Andrew's School gives more emphasis on the acquisition skills in reading that it overlooks the importance of attitudes and feelings of students toward reading. The results of this study became the basis of the proposed complementary reading program in grades in I to VI where recreational reading was given emphasis. This was done to enable St. Andrew's School to complement its reading program which was only a combination of developmental and functional reading.